Utilização do uso e ocupação da terra obtida por sensoriamento remoto na modelagem hidrológica - Rippel, Elzon Cassio (2020)
In recent decades, extreme rainfall-runoff events have increased significantly as a result of climate change and anthropogenic impacts at the global scale. Several authors have reported the influence of land use and land cover (LULC) in this scenario. However, the effects of LULC on the mechanisms that govern the flow generation process, especially in watersheds, are not yet fully understood. The use of hydrological modeling with tools such as remote sensing has been used by researchers to describe the hydrological processes in the catchments. A highlight has been the information obtained from vegetation indexes such as the Enhanced Vegetation Index (EVI2), from the product MOD13. This satellite provides an image with a spatial resolution of 250 m, with a temporal resolution of 16 days, used in applications that describes the vegetations parameter. Using EVI2 information, this work aimed to evaluate the feasibility of using EVI2 information to improve the space-time parameterization of the NCRS-CN method and the SWAT model, in the simulation of the flow generation of two rural watersheds, called WS80 (0.8 km²) and WS140 (1.39 km²), located in the municipality of Júlio de Castilhos, Rio Grande do Sul - Brazil. The simulations used monitored rain-runoff data between 2010 and 2012, using the Curve Number (CN-NRCS) and Soil and Water Assessment Tool (SWAT) models. For the CN-NRCS method, the results showed that there was a correlation between the initial abstraction parameter (Ia) and the LULC variations described by the EVI2 vegetation index, being possible to use the CN-NRCS method with initial abstraction ratio (λ) (variable) by obtaining Ia via EVI2, the performance of this approach was superior to the traditional ones, with λ fixed, in the simulation of the total runoff in the basin rain events. The SWAT model can simulate the flow when no data was available to watersheds, when the rotations crop observed by EVI2 are described and the model setup with the parameters of a neighboring basin (donor). EVI2 demonstrated potential, either as an exploratory or research tool, contributing to the understanding of the behavioral hydrological processes of runoff generation from the two watersheds.